Effect of IMRT and three-dimensional conformal radiotherapy on oral Candida colonization: A comparative study - Jasmine Shanthi Kamath; Raghavendra Kini; Anup Kumar Shetty; Vathsala Naik (Wolters Kluwer Medknow Publications, 2017)
Aim: To investigate oral candidiasis in patients with head and neck cancer before and after intensity-modulated radiation therapy and three-dimensional conformal radiotherapy (3D CRT) and to explore if there is an association with the type of radiotherapy used and the severity of candidiasis. Materials and Methods: Patients who received radiation therapy (RT) for the treatment of head and neck cancer were divided into two groups: Group 1 consisted of patients (n = 20) who received Intensity modulated radiation therapy (IMRT) and Group 2 (n = 20) consisted of patients who received 3D CRT. Saliva from these patients was collected before and after radiotherapy and evaluated for Candida species using culture method. Results: Significant increase of Candida albicans was seen in patients who underwent 3D CRT as compared to IMRT. Other species of Candida such as Candida tropicalis, Candida glabrata, and Candida krusei showed increase postradiotherapy in both groups, but the change was not significant. Conclusion: Although candidiasis is seen regardless of the type of radiation therapy used, the oral environment is more stable after intensity-modulated radiation therapy as and when compared to 3D CRT. Salivary substitutes and good oral hygiene before, during, and after radiotherapy could be used to increase oral clearance and to decrease the chance of candidiasis.